Análise genotípica do sistema de grupo sanguíneo dombrock em doadores de sangue do estado de Minas Gerais - Fabiana Chagas Camargos Piassi (2010)
Background: Data concerning the frequency of major blood group antigens of importance in transfusion medicine is essential to the development of rare red blood banks. Molecular approaches have enabled the detection of blood donors on a large scale when sera are not available for serological tests. The Dombrock system blood group is important in transfusion practice since hemolytic transfusion reactions related to its antibodies are reported. Moreover, the phenotypes: Gy(a-), Hy- and Jo(a-), originally describe in blacks, are considered rare by the International Society of Blood Transfusion. Dombrock blood group system genotyping has demonstrated various rearrangements of the DO gene in different populations. Single nucleotide polymorphisms (SNPs) have been associated with different alleles. New variants alleles had been identified in New York (DO*B-SH and DO*A-HA), in Africa (DO*B-SH-Q149K and DO* B-I175N) and in Brazil (DO*A-WL and DO*B-WL) and this considerable genetic diversity highlights the importance of regional research protocols for this blood group system. In Brazil previous studies conducted in São Paulo state showed higher prevalence of JO allele compared to HY. However due the high heterogeneity of Brazilian population, differences inside the country would be expected. Methods: The frequency of DO alleles in a southeast state of Brazil, Minas Gerais, was determined from the genotyping of 270 blood donors, by polymerase chain reaction and analysis of polymorphisms from the fragments resulting from digestion by restriction enzymes (PCR-RFLP) for the identification of the following SNPs: 323G/T (HY), 350C/T (JO), 793 (DO*A/DO* B) and 898C/G (HY*1/HY*2, DO*A-WL e and DO*B-WL). The prevalence of these alleles was compared with the donors described in the state of Sao Paulo. Donors with the HY and JO alleles were classified as white, black or brown according to the self-reported skin color at registration in order to evaluate a possible correlation between this variable and the presence of these alleles. Results: The HY allele frequency was approximately twice (2.41%) the JO allele (1.48%) and this prevalence of HY allele was statistically significantly higher (p<0,001) than the frequency in São Paulo (0,7%). In our study, we detected a homozygous state for HY. As well, the alleles DO*A-WL and DO*B-WL, recently described in São Paulo blood donors, were also founded in the state of Minas Gerais. The self-designation of skin color was related only to in HY allele. Conclusions: Our data confirm the diversity of Brazilian population and the different frequencies in DO alleles depending on the region studied. For the purpose of identification the Hy negative phenotype, this population could be the target in a screening. Despite the statistical correlation between the allele HY and the brown color skin, this information not predict the degree of African ancestry in admixed population and should not be applied as a variable in screening Hy- phenotype in Brazil